Extensive astrocyte metabolism of γ‐aminobutyric acid (GABA) sustains glutamine synthesis in the mammalian cerebral cortex. Issue 12 (25th June 2020) - Andersen, Jens V.; Jakobsen, Emil; Westi, Emil W.; Lie, Maria E. K.; Voss, Caroline M.; Aldana, Blanca I.; Schousboe, Arne; Wellendorph, Petrine; Bak, Lasse K.; Pinborg, Lars H.; Waagepetersen, Helle S.
Abstract: Synaptic transmission is closely linked to brain energy and neurotransmitter metabolism. However, the extent of brain metabolism of the inhibitory neurotransmitter γ‐aminobutyric acid (GABA), and the relative metabolic contributions of neurons and astrocytes, are yet unknown. The present study was designed to investigate the functional significance of brain GABA metabolism using isolated mouse cerebral cortical slices and slices of neurosurgically resected neocortical human tissue of the temporal lobe. By using dynamic isotope labeling, with [ 15 N]GABA and [U‐ 13 C]GABA as metabolic substrates, we show that both mouse and human brain slices exhibit a large capacity for GABA metabolism. Both the nitrogen and the carbon backbone of GABA strongly support glutamine synthesis, particularly in the human cerebral cortex, indicative of active astrocytic GABA metabolism. This was further substantiated by pharmacological inhibition of the primary astrocytic GABA transporter subtype 3 (GAT3), by ( S )‐SNAP‐5114 or 1‐benzyl‐5‐chloro‐2, 3‐dihydro‐1H‐indole‐2, 3‐dione (compound 34), leading to significant reductions in oxidative GABA carbon metabolism. Interestingly, this was not the case when tiagabine was used to specifically inhibit GAT1, which is predominantly found on neurons. Finally, we show that acute GABA exposure does not directly stimulate glycolytic activity nor oxidative metabolism in cultured astrocytes, but can be used as an additional substrate to enhance uncoupled respiration. These results clearly show that GABA is actively metabolized in astrocytes, particularly for the synthesis of glutamine, and challenge the current view that synaptic GABA homeostasis is maintained primarily by presynaptic recycling. Main Points: Both nitrogen and carbon GABA metabolism support astrocytic synthesis of glutamine in mouse and human brain slices. Cerebral cortical GABA metabolism is primarily mediated via astrocytic GAT3 uptake. Metabolism of GABA can enhance respiratory capacity in cultured astrocytes.